MMP Inhibitors on Dentin Stability: A Systematic Review and Meta-analysis. (August 2014) - Montagner, A.F.; Sarkis-Onofre, R.; Pereira-Cenci, T.; Cenci, M.S.
The aim of this study was to systematically review the literature for in vitro and ex vivo studies that evaluated the effect of matrix metalloproteinase (MMP) inhibitors during the adhesive procedure on the immediate and long-term resin-dentin bond strength. The search was conducted in 6 databases with no publication year or language limits, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. From 1, 336 potentially eligible studies, 48 were selected for full-text analysis, and 30 were included for review, with 17 considered in the meta-analysis. Two reviewers independently selected the studies, extracted the data, and assessed the risk of bias. Pooled effect estimates were expressed as the weighted mean difference between groups. The most used MMP inhibitor was chlorhexidine (CHX). Immediate bond strength results showed no difference between 2% CHX and control; however, a difference was found between 0.2% CHX and control at baseline. After aging, CHX presented higher bond strength values compared to control groups ( p < .05). However, this was not observed for longer periods of aging. High heterogeneity was found in some comparisons, especially for the water storage aging subgroup. Subgroup analyses showed that self-etching and etch-and-rinse adhesives are benefited by the CHX use. From the studies included, only 1 presented low risk of bias, while the others showed medium or high risk of bias. The use of MMP inhibitors did not affect the immediate bond strength overall, while it influenced the aged bond strength. Aging procedures influenced bond strength values of the dentin adhesion stability.